Cronología del Conflicto Social: Cuaderno de Trabajo No. 260 - Mora Solano, Sindy (2008)
UCR::Vicerrectoría de Investigación::Unidades de Investigación::Ciencias Sociales::Instituto de Investigaciones Sociales (IIS)